2019
DOI: 10.1111/pim.12630
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity and blood cytokine concentrations in dogs with natural Babesia rossi infection

Abstract: Aims Babesia rossi causes severe disease in dogs. Here, we describe the association between serum cytokine concentrations and disease severity. Methods Seventeen controls and 55 PCR confirmed B rossi‐infected dogs were included. Diseased dogs were subdivided into 23 critically ill and 32 relatively well cases. Serum concentrations of 11 cytokines and biochemical markers of disease severity were determined. Results Significant differences were detected for IL‐6, IL‐8, IL‐10, MCP‐1 and TNF‐α between the groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 53 publications
1
66
2
Order By: Relevance
“…Macrophages not only initiate and perform phagocytosis, but they also release cytokines and chemokines all of which mediate pathogen clearance and affect splenic cellular arrangement. The cytokines of macrophage origin (such as TNFa and MCP‐1) have also been shown to be elevated in B. rossi and are associated with disease severity and outcome . Selective depletion of monocyte‐macrophages in mice chronically infected with Babesia microti impaired host protection against subsequent lethal infection with Babesia rodhani, showing that these cells are critical for cross‐protective immunity against B. rodhaini , conferred by B. microti in mice .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages not only initiate and perform phagocytosis, but they also release cytokines and chemokines all of which mediate pathogen clearance and affect splenic cellular arrangement. The cytokines of macrophage origin (such as TNFa and MCP‐1) have also been shown to be elevated in B. rossi and are associated with disease severity and outcome . Selective depletion of monocyte‐macrophages in mice chronically infected with Babesia microti impaired host protection against subsequent lethal infection with Babesia rodhani, showing that these cells are critical for cross‐protective immunity against B. rodhaini , conferred by B. microti in mice .…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages not only initiate and perform phagocytosis, but they also release cytokines and chemokines all of which mediate pathogen clearance and affect splenic cellular arrangement. The cytokines of macrophage origin(such as TNFa and MCP-1) have also been shown to be elevated in B. rossi and are associated with disease severity and outcome 37.…”
mentioning
confidence: 99%
“…Similarly, the study by Leisewitz et al (8) showed that IL-6, MCP-1, as well as tumor necrosis factor (TNF)-α were significantly higher in B. rossi-infected non-survivors compared to those that survived (8). Interestingly, IL-8 was found to be negatively correlated with disease severity for both studies, with the control group having higher concentrations than either survivors or non-survivors (8).…”
Section: Introductionmentioning
confidence: 78%
“…The severity of the disease has been reported to be due to an exuberant and ineffective immune response that sometimes results in lethal collateral organ damage (3)(4)(5)(6). Recent studies have confirmed the presence of a marked pro-inflammatory response in dogs infected with B. rossi, of which the severity was correlated with patient outcome (7,8). The study by Goddard et al (7), of which some of the published data will be used in our study, reported that concentrations of interleukin (IL)-2, IL-6, IL-8, IL-10, IL-18, monocyte chemotactic protein (MCP)-1, and granulocyte-macrophage colony stimulating factor (GM-CSF), were correlated with the severity of the pro-inflammatory response and outcome, in B. rossi-infected dogs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it must be remembered that the damage to the host is more the consequence of the host’s immune response to the infection, than direct damage by the parasite [ 17 ]. During babesiosis a cytokine storm is observed, which is a response to multiple organ damage, including the testicles.…”
Section: Resultsmentioning
confidence: 99%